Diaphragmatic fenestration an effective treatment for refractory postoperative chylothorax: a case report - Akanbi, Oluwaseun R.; Vaidyanathan, Swaminathan; Agarwal, Prakash; Musthafa, Janeel; Solomon, Neville A. G. (International Journal of Research in Medical Sciences, 2020)
Postoperative chylothorax remains a clinical challenge to the surgeon with substantial morbidity and risk of mortality. Though an uncommon complication, it is known to complicate cardiac and non-cardiac thoracic surgeries. Conservative measures are first employed in managing this. Surgical options are adopted when the effusion is protracted, most recent of which includes diaphragmatic fenestration. A 9-year-old girl is presented who developed recurrent right chylothorax following thoracoscopic excision of a cystic lymphangioma. Following failed conservative therapy, she had thoracic duct ligation and right diaphragmatic fenestration (using fenestrated polytetrafluoroethylene patch) with satisfactory outcome. Aetio-pathologic mechanisms implicated in postoperative chylothorax have been classified into traumatic (iatrogenic injury to the thoracic duct or its branches) and non-traumatic. With initial conservative measures (repeated pleural aspirations and intercostal drainage, medium chain triglyceride/ low fat feeds or alternatively, fasting and total parenteral nutrition) spontaneous closure remains unpredictable. Diaphragmatic fenestration when employed resulted in faster resolution of effusion and earlier commencement of enteral feeding with no significant complication. Diaphragmatic fenestration is effective and safe for treating refractory post-operative chylothorax.